Mobility in a Post-Pandemic City: Subjective Considerations Based on Observations and âThe Plagueâ by Albert Camus - Jacek SzoÅtysek (The Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
The functioning of the city during a pandemic under the influence of social isolation forced by the state authorities and the suspension of a significant part of economic activity forced by administrative decisions causes changes in the minds of the city's inhabitants. This will highly likely translate into a new image of the city in the post-pandemic period. The aim of this article is to review the antecedents of the functioning of the post-pandemic city and to outline the premises of probable changes in the mobility of the inhabitants of the post-pandemic city. The aim is to point out the changes that occur as a result of responding to the pandemic in sudden reaction mode, which are likely to occur again in the future and are related to the consequences described inductively as the following sequence: inhabitants' emotions